1976
DOI: 10.2134/jeq1976.00472425000500010019x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrates Following Four Years Continuous Corn and as Surveyed in Irrigated Farm Fields of Central and Eastern Colorado

Abstract: High rates of fertilizer N used in many intensive farm management systems have been cited as a potential pollution hazard to surface and ground waters. The purpose of this study was to evaluate soil NO3− accumulations following 4 years continuous corn (Zea mays L.) grown with different nitrogen and irrigation regimes, and to compare these results to present NO3− concentrations found in irrigated farm fields of central and eastern Colorado. Soil NO3− content in the 300‐cm sampled profile was significantly influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This observation is supported by an adjacent 15 N fertilizer study with onion and corn by Halvorson et al (2002), who found fertilizer N was leached to 180‐cm depth the year of application to an onion crop and was still present after harvest of the following corn crop with no additional fertilizer N applied. Ludwick et al (1976) reported NO 3 –N leached below the rooting depth of irrigated corn with increasing NO 3 –N levels as N fertilizer application rate increased.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is supported by an adjacent 15 N fertilizer study with onion and corn by Halvorson et al (2002), who found fertilizer N was leached to 180‐cm depth the year of application to an onion crop and was still present after harvest of the following corn crop with no additional fertilizer N applied. Ludwick et al (1976) reported NO 3 –N leached below the rooting depth of irrigated corn with increasing NO 3 –N levels as N fertilizer application rate increased.…”
Section: Discussionmentioning
confidence: 99%
“…I rrigation and fertilization provide effective means to increase crop yield in the Great Plains (Wienhold et al, 1995; Norwood, 2000). However, improper irrigation and fertilization management is also a major contributor to water contamination and water resource shortages (Ludwick et al, 1976; Al‐Kaisi et al, 1997, 1999). Increasing uses of irrigation and fertilization in the Great Plains have raised concern regarding ways of managing water and nutrients (especially N) more efficiently to overcome excessive irrigation and nutrient losses.…”
mentioning
confidence: 99%
“…moisture (Ludwick et al, 1976). Excess N in the soil is also susceptible to loss by other mechanisms such as plant loss as ammonia (NH 3 ), denitrification, surface runoff, leaching and volatilization (Raun and Johnson, 1999) thereby reducing NUE Table 3.…”
Section: Nitrogen Responsementioning
confidence: 99%